2020
DOI: 10.3390/w12010301
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Tuned Machine Learning Technique for Abutment Scour Depth in Clear Water Condition

Abstract: Abutment scour is a complex three-dimensional phenomenon, which is one of the leading causes of marine structure damage. Structural integrity is potentially attainable through the precise estimation of local scour depth. Due to the high complexity of scouring hydrodynamics, existing regression-based relations cannot make accurate predictions. Therefore, this study presented a novel expansion of extreme learning machines (ELM) to predict abutment scour depth (ds) in clear water conditions. The model was built u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 67 publications
1
12
0
Order By: Relevance
“…This is in accordance with the outcomes of the r value and the determination of the most effective input parameter combination. Also, our result is in accordance with Bonakdari et al (2020) which stated that the relative median sediment diameter (d50/l) is the most effective parameter for the prediction of scour depth. Bonakdari et al…”
Section: Sensitivity Analysissupporting
confidence: 92%
See 4 more Smart Citations
“…This is in accordance with the outcomes of the r value and the determination of the most effective input parameter combination. Also, our result is in accordance with Bonakdari et al (2020) which stated that the relative median sediment diameter (d50/l) is the most effective parameter for the prediction of scour depth. Bonakdari et al…”
Section: Sensitivity Analysissupporting
confidence: 92%
“…Our results show that the approach flow depth (h) is not very effective on the overall scour depth, while flow velocity, transverse abutment length, and median sediment diameter are important. Azimi et al, (2019), Moradi et al, (2019) and Bonakdari et al, (2020) revealed that their best input combination was a combination of Fe, h/l, Ks, d50/l. This definitely shows that the structure of the modeling approach has a crucial role on the selection of the input combination, which is resulting from different structure of each model.…”
Section: Sensitivity Analysismentioning
confidence: 99%
See 3 more Smart Citations